PENERAPAN NILAI-NILAI MULTIKULTURALISME MELALUI METODE BIMBINGAN KELOMPOK UNTUK MENINGKATKAN BUDAYA TOLERANSI SISWA DI SMK SETIA ATMADJA JEMBER - Arifin Nur Budiono (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2013)
The implementation of multiculturalism value through group councelling to increase tolerent behaviour among the students at SMK Admadja Jember. This group councelling involved the tenth and eleventh grade students of SMK Admadja Jember as the subjects. This research was a counselling action research which was implemented in two cycles considering the time span and the researcher’s level of ability. Specifically, action cycle II was conducted due to the absence of intended target. In general,the result of this action research can be concluded that the implementation of multiculturism value could increase tolerant behaviour among the students of SMK Admadja Jember. It could be seen through how the students could respect others’ opinion, sypathetic manner of expressing opinion, accepting group’s decision, positive view on deversity, and the spirit of togetherness. The subjects considered that deversity was a gift for sharing and supportiveness.Key Words : Multiculturalism  Value, Tolerant